Analýza bezpečnosti v provozu civilního letectví ČR v letech 2003-2010 - Gubani, Ondřej (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2012)
Diplomová práce se zabývá analýzou příčin událostí v provozu civilního letectví České republiky za období 2003 - 2010. Na základě analýzy závěrečných zpráv leteckých událostí byly popsány příčiny vzniku těchto událostí. V závěru práce jsou dosažené výsledky porovnány s historickým vývojem nehodovostí civilního letectví v ČR.

This diploma thesis deals with analysis of causes of events in civil aviation operation in the Czech Republic during the period 2003 - 2010. Based on the analysis of final reports about flight incidents, there were described causes of these events. In conclusion the obtained results are compared with historical development of civil aviation incidents in the Czech Republic
Analysis of traffic safety in civil aviation of the Czech Republic in the years 2003-2010
Keywords: Incident; vážný incident; letecká nehoda; příčina; šetření leteckých nehod.; Incident; serious incident; accident; investigation of accidents.